Enzyme-linked immunosorbent assay and polymerase chain reaction in the laboratory diagnosis of human granulocytic anaplasmosis - V. Yu. Teterin; E. I. Korenberg; V. V. Nefedova; N. N. Vorob’ova; V. I. Frizen (Журнал инфектологии, 2014)
With the help of enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) in 332 patients with acute feverish illness after a tick bite, treated at the Perm Regional Hospital of Infectious Diseases in the spring-summer period of 2010, the diagnostics of human granulocytic anaplasmosis was performed. By Omnix’s testsystems HGA-ELISA-IgM and HGA-ELISA-IgG 845 serum, as well as by «nested» PCR, using primers ge3a1-ge10r2 and ge9f3-ge2r4 for A. phagocytophilum genetic material amplification, 952 samples of dried blood spots were studied in the dynamics of the disease. The optimal period for the use of ELISA and PCR was determined. Anaplasmosis was confirmed by both methods in 79 patients (ELISA – in 68, PCR –in 25). In general, serodiagnosis, particularly ELISA, and PCR should be regarded not as alternative but as complementary to each other’s methods of laboratory diagnosis of anaplasmosis.